Development of printed and flexible dry ECG electrodes - Chlaihawi, Amer Abdulmahdi; Narakathu, Binu Baby; Emamian, Sepehr; Bazuin, Bradley J.; Atashbar, Massood Z. (Sensing and Bio-Sensing Research, 2018)
Printed, flexible and wearable dry electrodes for monitoring electrocardiogram (ECG) signals, without any skin preparation and use of wet gel, has been developed. Silver (Ag) flake ink was screen printed on a flexible polyethylene terephthalate (PET) substrate to fabricate the dry ECG electrode. Multi-walled carbon nanotube (MWCNT)/polydimethylsiloxane (PDMS) composite, as a conductive polymer, was then deposited on the printed Ag electrode by using a bar coating technique. The performance of the printed electrodes was investigated by testing the MWCNT/PDMS composite conductivity and measuring the electrode-skin impedance for electrode radii varying from 8 mm to 16 mm. It was observed that the dry ECG electrode, with the largest area, demonstrated better performance, in terms of MWCNT/PDMS composite conductivity, ECG signal intensity and correlation when compared to a commercial wet silver/silver chloride (Ag/AgCl) electrode. In addition, the capability of the dry ECG electrodes for monitoring ECG signals in both the relaxed sitting position and while the subject is in motion, was also investigated and the results were compared with a wet Ag/AgCl ECG electrode (T716). While the subject is in motion, the printed dry electrodes were less noisy and were able to better identify the typical ECG characteristics in the signals due to its better conformal contact at the electrode-skin interface. The results obtained demonstrated the feasibility of employing conventional screen printing process for the development of flexible dry ECG electrodes for applications in the biomedical industry. •Printed, flexible and wearable dry electrodes were developed to monitor ECG signals.•The capability of the dry electrodes were investigated by measuring ECG signals.•The dry ECG electrode demonstrated better performance than commercial wet electrode.•The dry electrodes provide better conformal contact at the electrode-skin interface.